"Float like a butterfly, sting like a bee" : giving voice to planning practitioners - Tasan-Kok, Tuna; Bertolini, Luca; Oliveira e Costa, Sandra; Lothan, Hila; Carvalho, Higor; Desmet, Maarten; De Blust, Seppe; Devos, Tim; Kimyon, Deniz; Zoete, J. A.; Ahmad, Peter (Planning theory & practice, 2016)
A special section of this journal that brings together essays that each offer a critical reflection on the major challenges faced by planning practitioners.